ASPEK HUKUM PEMBANGUNAN PERUMAHAN PASCA PUTUSAN MAHKAMAH KONSTITUSI (MK) BAGI MASYARAKAT BERPENGHASILAN RENDAH (MBR) - Hudi Karno Sabowo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2013)
In Indonesia, according to information from Deputi Bidang Pembiayaan Kementerian Perumahan Rakyat, there are millions of people who do not own their own home. The problem that frequently encountered is the problem of lack of funds. Distribution of the mortgages loan had not yet reached the low-income people. The potential distribution of mortgages loan for low-income people reached 34 million people. However, opportunities for low-income people to have decent housing was constrained by the government with the issuance of Undang-Undang Nomor 1 Tahun 2011 on Housing and Settlement Region set a minimum floor area of 36m2 house (square meters). With that restriction the price of the house would become increasingly unaffordable for the low-income people. Constraints are contained in Article 22 paragraph (3). The full written are thus